2013
DOI: 10.1530/jme-12-0231
|View full text |Cite
|
Sign up to set email alerts
|

Rat Gnrhr promoter directs species-specific gene expression in the pituitary and testes of transgenic mice

Abstract: The GnRH receptor (GnRHR) is expressed in several non-pituitary tissues, notably in gonads. However, mechanisms underlying the gonad-specific expression of Gnrhr are not well understood. Here, Gnrhr expression was analysed in the developing testes and pituitaries of rats and transgenic mice bearing the human placental alkaline phosphatase reporter gene (ALPP) under the control of the rat Gnrhr promoter. We showed that the 3.3 kb, but not the pituitary-specific 1.1 kb promoter, directs ALPP expression exclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 65 publications
1
10
1
Order By: Relevance
“…Receptors for LH, prolactin and GNRH have all been shown in earlier studies to be expressed in rat Leydig cells (Zhang et al 1995, Ariyaratne et al 2000, Ishaq et al 2013), but others have not been described previously. GPR182 is an adrenomedullin receptor that mediates a cAMP response to the peptide (Kapas et al 1995).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Receptors for LH, prolactin and GNRH have all been shown in earlier studies to be expressed in rat Leydig cells (Zhang et al 1995, Ariyaratne et al 2000, Ishaq et al 2013), but others have not been described previously. GPR182 is an adrenomedullin receptor that mediates a cAMP response to the peptide (Kapas et al 1995).…”
Section: Discussionmentioning
confidence: 90%
“…There are also some known differences in Leydig cell function between the species (e.g. Gnrhr is expressed in the rat testis but not the mouse testis (Ishaq et al 2013)), while a number of mouse transcripts in the Sanz et al (2013) study showed low expression in the rat arrays so that any effect of EDS would be difficult to show (e.g. Fetub).…”
Section: Discussionmentioning
confidence: 99%
“…The 3.3‐Gnrhr‐ALPP mice were first used to analyse the spatial and temporal patterns of rat promoter activity during development in the hippocampus and testis. In both cases, we found that, in the transgenic mouse, the developmental profile of ALPP expression driven by the 3.3‐kb rat Gnrhr promoter reflected the expression pattern of Gnrhr in rat . Indeed, in the testis, ALPP transgene and rat Gnrhr expression was detected during foetal life and displayed the same biphasic profile characterised by high mRNA levels around birth, which initially declined and subsequently increased progressively at the end of the pre‐pubertal period (Fig.…”
Section: Species Specificities In the Mechanisms Regulating Gnrhr Expmentioning
confidence: 68%
“…In a third context, namely the adult pituitary after gonadectomy, the transgene was strongly up‐regulated. This mimicked the castration‐induced responsiveness of the rat Gnrhr but contrasted with the endogenous mouse Gnrhr , which was not significantly affected by castration . In parallel, using in situ analysis of transgene expression, we could localise rat Gnrhr promoter activity in a subset of neurones in the hippocampus and in foetal Leydig cells and progenitors of the adult Leydig cell population in the testis .…”
Section: Species Specificities In the Mechanisms Regulating Gnrhr Expmentioning
confidence: 78%
See 1 more Smart Citation